Rencana Strategis Pengembangan Sumber Daya Pendidik di SD IT Al-Ihsan Lubuk Tarok Kabupaten Sijunjung - Fatris, Yuli; Mudarti, Hasni; Asmendri, Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to explain how to develop educational resources especially for teachers at SD IT Al-Ihsan Lubuk Tarok, Sijunjung Regency. This research was conducted using a qualitative descriptive approach. Data collection is carried out through interviews, observations and documentation. Data analysis starts from an effort to find meaning starting with data collection, then data reduction, data presentation and verification. The results of the research carried out planning for the selection or recruitment of teaching staff, planning for developing educational resources to improve the quality of educators, improving the quality of educational organizations, determining the time for implementing the planning activities, evaluating teaching staff, supervision, providing compensation, as well as obstacles and obstacles encountered when strategically planning the development of teaching resources. From the results of the research, it can be concluded that the strategic plan for developing teaching resources at SD IT Al-Ihsan Lubuk Tarok has been running properly. However, there are still areas that need to be improved in terms of development plans for evaluation of programs that have been planned by schools and foundations